A COMPARITIVE STUDY OF TOPICAL MINOXIDIL (5%) PLUS FINASTERIDE (0.1%) VERSUS PLATELET-RICH PLASMA PLUS TOPICAL MINOXIDIL (5%) PLUS FINASTERIDE (0.1%) IN PATIENTS WITH ANDROGENIC ALOPECIA - DHARA D PATEL; SOM J LAKHANI; SPANDAN K SHAH; KRUNAL TRALSAWALA; ARTI K BHABHOR (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objective: Androgenic alopecia is progressive loss of terminal hairs in patterned distribution. It causes psychoemotional problems and affects the quality of life. Therefore, to achieve optimal results, multiple modalities are required. In this study, the combination of platelet-rich plasma (PRP) along with topical drugs such as minoxidil and finasteride is compared with the conventional combination of topical minoxidil (5%)+Finasteride (0.1%) Methods: A prospective randomized study was conducted on a total of 50 males with androgenetic alopecia (AGA) at the Department of Dermatology, Parul Institute of Medical Sciences and Research for 1 year. A total of 50 males diagnosed with AGA were divided into two groups randomly. Patients in in Group A were recommended topical minoxidil (5%)+finasteride (0.1%), and Group B was treated with PRP along with topical minoxidil (5%)+finasteride (0.1%). PRP was done every month for 6 months and minoxidil applied over scalp twice daily for 6 months. Both groups were followed up monthly for 6 months and then after 6 months of last visit. Hair density was assessed using the Hamilton–Norwood scale using photographs and patient’s self-assessment scores. Data were evaluated applying Chi-square test. Results: After 6 months of the last visit subjective response with minoxidil (5%) +finasteride (0.1%) showed good response in 26%, moderate in 39%, and poor in 35%, whereas PRP+minoxidil (5%)+finasteride (0.1%) group showed good response in 65%, 26% responded moderately and 9% responded poorly. Conclusion: The combination therapy of PRP and topical minoxidil+finasteride being safe and effective can be used for patients unresponsive to conventional therapy and for faster outcome.